Anmeldelser - Fjeldsøe, Michael (Danish Yearbook of Musicology, 2009)
Review of: Nicholas Cook: The Schenker Project. Culture, Race, and Music Theory in Fin-de-siècle Vienna. Oxford and New York: Oxford University Press, 2007